Icariin Prevents Amyloid Beta-Induced Apoptosis via the PI3K/Akt Pathway in PC-12 Cells - Zhang, Dongdong (Evid Based Complement Alternat Med, 2015)
Icariin is a prenylated flavonol glycoside derived from the Chinese herb Epimedium sagittatum that exerts a variety of pharmacological activities and shows promise in the treatment and prevention of Alzheimer's disease. In this study, we investigated the neuroprotective effects of icariin against amyloid beta protein fragment 25–35 (Aβ (25–35)) induced neurotoxicity in cultured rat pheochromocytoma PC12 cells and explored potential underlying mechanisms. Our results showed that icariin dose-dependently increased cell viability and decreased Aβ (25–35)-induced apoptosis, as assessed by MTT assay and Annexin V/propidium iodide staining, respectively. Results of western blot analysis revealed that the selective phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002 suppressed icariin-induced Akt phosphorylation, suggesting that the protective effects of icariin are associated with activation of the PI3K/Akt signaling pathway. LY294002 also blocked the icariin-induced downregulation of proapoptotic factors Bax and caspase-3 and upregulation of antiapoptotic factor Bcl-2 in Aβ (25–35)-treated PC12 cells. These findings provide further evidence for the clinical efficacy of icariin in the treatment of Alzheimer's disease.